PERSEPSI GURU PAMONG TENTANG KOMPETENSI MAHASISWA TATA RIAS DAN KECANTIKAN DALAM PELAKSANAAN PPLK PADA SMK DI SUMBAR - PUTRI, SYOFIA MELISA; katin, yusmar emmy; hayatunnufus, hayatunnufus (Journal of Home Economics and Tourism, 2013)
This study aimed to describe the practice of Student TeacherTeaching Competency Education D4 Makeup and Beauty inEducation Field Experience Program Implementation (PPLK) atvocational schools in West Sumatra. This research is descriptivequantitative. The population in this study were all teachers who haveled officials in conducting PPLK students at vocational schools inWest Sumatra, which totaled 19 people. The research instrumentused questionnaires using a Likert scale instrument validity andreliability have been analyzed and then the data is described usingpredefined categories of assessment to analyze the scores obtainedfrom each of the assessment indicators. Based on the results of dataanalysis obtained results are indicators of competency masterylearning materials students obtained the highest level of achievementrespondents unfavorable category with a score of 36.84%, anindicator of management competence learning program gained thehighest level of achievement in the category of respondents with ascore of 31.57 %, an indicator of competence using instructionalmedia respondents obtained the highest level of achievement in bothcategories with a score of 36.84%, an indicator of competencyAssessment of student learning outcomes obtained the highest levelof achievement respondents unfavorable category with a score of42.10%.Keyword: Persepsi Guru Pamong, Kompetensi Mahasiswa, Mahasiswa PPL